Improving the Design of Youth Innovative - Creative and Development Scientific Centers - Hasanov Azamat Ozodovich; Qosimov Ilhom Maribovich (Genius Publishing Group, 2022)
The innovation center proposed by the author in this article serves to strengthen the practical application of theoretical knowledge. It is expedient to have the following general sections within the innovation centers and which is to be considered on their designing for the purpose. Department of Education (theoretical knowledge is further enriched); Research Department (works on scientific research and ideas); Production department (samples are produced); Exhibition area; Department of Commercialization (developments are commercialized and put into practice). By designing separate buildings and experimental rooms in each direction, it is planned to create great opportunities for young people to put their innovative proposals into practice. Interest, motivation and end results motivate young people to strive for innovation and creativity. The study of developed countries shows that the innovation center for the development of the state has risen to the level of public policy, along with theoretical knowledge, practice is required of young people simultaneously
Keywords: Architecture; innovation; center; creative person